Profile and Outcome of Triple Negative Breast Cancer at a Tertiary Care University Hospital in Nepal - Khanal, Suman; Singh, Yogendra P.; Sayami, Gita; Ozaki, Akihiko (Asian Pacific Journal of Cancer Care, 2020)
Background: TNBC (Triple negative breast cancer) subtype (ER-/PR-/HER2-) of breast cancers are known for aggressive tumor biology and poor survival prospects, with high early relapse rate. However, little is known about the prevalence and characteristics of TNBC breast cancer in Nepal. Objectives: To clarify the geographical distribution, clinical profile and outcome of TNBC patients when compared with non-TNBC patients managed in tertiary care university hospital in Nepal. Materials and Methods: This is a study on prospective observational analyses of TNBC and non-TNBC patients managed at Tribhuvan University Teaching Hospital, Kathmandu from October 2015-March 2018. We collected and analyzed data on clinical profile, pathological tumor features and outcome of the two patient groups. Results: A total of 108 breast cancer patients were included in our study, 38 (35.2%) of which were TNBCs. Mean age at diagnosis was 49±12 years. Majority of TNBCs (29%) were concentrated in Terai districts compared to non-TNBCs (18.6%). Among TNBCs, 15.2% had tumor size 5 cm or more while only 11.9% had such finding in non-TNBCs. Majority of TNBCs and non-TNBCs were of invasive ductal carcinoma of NST histology (76.3 vs 90%). TNBC tumors were significantly of grade 3 (P value=0.003). Perineural invasion was seen more (15.8%) in TNBCs compared to 8.96% in non-TNBCs. On average, 23.6% of total nodes retrieved from axilla were positive for tumor in TNBCs compared to 21% in non-TNBCs. Three patients developed metastases in TNBCs of which two were to brain while 5 had metastases in non-TNBC with none to brain. Higher percentage of patients died in TNBC group (13.2 vs 7.1%). Conclusions: TNBCs are quite common, higher grade tumors with brain metastasis without particular geographic distribution.